Placement and Displacement: Questions of ‘Contextual’ Mickiewiczology - Banowska, Lidia (Porównania, 2021)
The author reflects on how Mickiewicz and his work is contextualised and recontextualised in the work collected in the volume Mickiewicz kontekstowy (Contextual Mickiewicz). The analysis is a manifestation of perceiving phenomena through a network of complex mutual relations (both intra- and extra-literary) and attempting to understand through situating, and exemplifies the relevance of reading that is open to other times, other spheres (national, cultural, aesthetic), and ultimately, other perspectives. The collection is “constellational”, and is expressed in the diverse problems, approaches and methodologies that are taken up. The images of Mickiewicz that emerge from this study are the effect of two perspectives that are concurrent and in dialogue with each other: central views (emphasising Mickiewicz’s community-forming value) and peripheral views (his lesser-known qualities, including those of a mystic, author of erotic poems or a poet translated into the language of other arts).